Integrating Culturally Responsive Teaching in EFL Classrooms - Muhammad Adzha Yoanduanda; Halim, Abdul; Sunarti (Borneo Educational Journal (Borju), 2025)
This study aimed to explore the effectiveness and challenges in integrating Culturally Responsive Teaching (CRT) in English as a Foreign Language (EFL) classrooms. CRT had been recognized as an effective approach to addressing the diverse cultural and linguistic backgrounds of learners in EFL classrooms. However, integrating CRT strategies in language teaching remained a challenge due to curriculum constraints, teacher preparedness, and classroom dynamics. This study used a mixed-methods approach, applying both qualitative and quantitative methods with a case study design. The participants included EFL teachers and learners. Data were collected through Google Forms, semi-structured interviews, classroom observations, and document analysis related to teaching practices. This study involved 27 EFL students and 2 teachers using a mixed-methods approach, including pre- and post-tests, interviews, and observations. Quantitative results analyzed via paired-sample t-tests showed significant improvement (p = 0.001) in language proficiency after implementing CRT. The data were analyzed using descriptive statistics to identify patterns regarding effectiveness and thematic analysis to explore the challenges of implementing CRT in EFL classrooms.